Solving Constraint Satisfaction Problems with Networks of Spiking Neurons - Jonke, Zeno; Habenschuss, Stefan; Maass, Wolfgang (Frontiers in Neuroscience, 2016)
Network of neurons in the brain apply – unlike processors in our current generation of computer hardware – an event-based processing strategy, where short pulses (spikes) are emitted sparsely by neurons to signal the occurrence of an event at a particular point in time. Such spike-based computations promise to be substantially more power-efficient than traditional clocked processing schemes. However it turned out to be surprisingly difficult to design networks of spiking neurons that can solve difficult computational problems on the level of single spikes (rather than rates of spikes). We present here a new method for designing networks of spiking neurons via an energy function. Furthermore we show how the energy function of a network of stochastically firing neurons can be shaped in a quite transparent manner by composing the networks of simple stereotypical network motifs. We show that this design approach enables networks of spiking neurons to produce approximate solutions to difficult (NP-hard) constraint satisfaction problems from the domains of planning/optimization and verification/logical inference. The resulting networks employ noise as a computational resource. Nevertheless the timing of spikes (rather than just spike rates) plays an essential role in their computations. Furthermore, networks of spiking neurons carry out for the Traveling Salesman Problem a more efficient stochastic search for good solutions compared with stochastic artificial neural networks (Boltzmann machines) and Gibbs sampling.